Profil Kemandirian Belajar Siswa Menengah Atas - Ora, Maria Haba; Taneo, Joris; Loban, Maria Natalia (Universitas PGRI Semarang, 2024)
This study aims to describe the learning independence of senior high school students at SMA Negeri 1 Lamboya. The research population consisted of 218 students and samples taken from a portion of the population were 131 students. Data collection techniques used in this study using the questionnaire method. While the research instrument uses a sheet of learning independence scale (Liker scale). The data analysis technique uses tabulation, namely grouping data into frequency tables to facilitate analysis. The results showed that the profile of the learning independence of SMA Negeri 1 Lamaboya students was mostly in the score interval category between 128-138 with a score of 50, 38% being in the sufficient category. 39 or 29.77% are in the low category, the high category is at a score of 17.56% and very high is at a score of 2.29%.